PENGARUH RISIKO KREDIT, SUKU BUNGA DAN LIKUIDITAS TERHADAP PROFITABILITAS PERBANKAN DI INDONESIA SEBELUM DAN PADA SAAT KONDISI PANDEMI COVID-19 - Made, I Made Sudarmaja Putera; Suhartoko, Yohanes Berchman (Universitas Katolik Indonesia Atma Jaya, 2025)
The banking industry in Indonesia is one of the backbones of the economy which has an intermediation function, namely channeling funds collected from the public in the form of savings and distributing loans or credits to the real business sector in efforts to develop businesses. This research aims to determine the effect of credit risk as measured by Non Performing Loans (NPL), interest rate risk as measured by Net Interest Margin (NIM) and liquidity risk as measured by Loan to Deposit Ratio (LDR) on profitability as measured by Return On Assets (ROA) and Return On Equity (ROE) of banking, especially Bank Group Based on Core Capital (KBMI) 4 in Indonesia before the Covid-19 pandemic (quarterly period 2015-2019) and during the Covid-19 pandemic (quarterly period 2020-2022). The data analysis method used in this research uses panel data analysis, Random Effect Model (REM) using the Eviews version 12 statistical program. The results of the analysis in this study show that credit risk as measured by NPL has a significant positive influence on profitability as measured by ROA, interest rate risk as measured by NIM has a significant positive influence on profitability as measured by ROA, liquidity risk as measured by LDR has an insignificant influence. on profitability as measured by ROA and during the 2020-2022 Covid-19 pandemic, changes in profitability as measured by ROA had an insignificant influence, credit risk as measured by NPL had a significant positive influence, interest rate risk as measured by NIM had an influence which is not significantly negative, liquidity risk as measured by LDR has a significantly positive effect. Then credit risk as measured by NPL has an insignificant positive effect on profitability as measured by ROE, interest rate risk as measured by NIM has a significant positive effect on profitability as measured by ROE, liquidity risk as measured by LDR has a significant positive effect on profitability as measured with ROE and during the 2020-2022 Covid-19 pandemic, profitability as measured by ROE had an insignificant influence. Keywords: NPL, NIM, LDR, ROA, ROE, KBMI, Covid-19 pandemic, credit risk, interest rate risk, liquidity risk.